Effects of a freeze-dried juice blend powder on exercise-induced inflammation, oxidative stress, and immune function in cyclists - Knab, A. M.; Nieman, D. C.; Gillitt, N. D.; Shanely, R. A.; Cialdella-Kam, L.; Henson, D.; Sha, W.; Meaney, M. P. (Applied Physiology, Nutrition, and Metabolism, 2014)
A freeze-dried fruit and vegetable juice powder (JUICE) was investigated as a countermeasure nutritional strategy to exercise-induced inflammation, oxidative stress, and immune perturbations in trained cyclists. Thirty-four cyclists (25 male, 9 female) were randomized to control (nonJUICE) or JUICE for 17 days. JUICE provided 230 mg·day-1 of flavonoids, doubling the typical adult daily intake. During a 3-d period of intensified exercise (days 15-17), subjects cycled at 70%-75% VO2max for 2.25 h per day, followed by a 15-min time trial. Blood samples were collected presupplementation, post supplementation (pre-exercise), and immediately and 14-h post exercise on the third day of exercise. Samples were analyzed for inflammation (interleukin (IL)-6, IL-8; tumor necrosis factor alpha (TNFa); monocyte chemoattractant protein-1 (MCP-1)), oxidative stress (oxygen radical absorbance capacity (ORAC), ferric reducing ability of plasma (FRAP), reduced and oxidized glutathione, protein carbonyls), and innate immune function (granulocyte (G-PHAG) and monocyte (M-PHAG) phagocytosis and oxidative burst activity). A 2 (group) × 4 (time points) repeated measures ANOVA revealed significant time effects due to 3 days of exercise for IL-6 (396% increase), IL-8 (78% increase), TNFa (12% increase), MCP-1 (30% increase), G-PHAG (38% increase), M-PHAG (36% increase), FRAP (12.6% increase), ORAC (11% decrease at 14 h post exercise), and protein carbonyls (82% increase at 14 h post exercise) (p < 0.01). No significant interaction effects were found for any of the physiological measures. Although providing 695 gallic acid equivalents of polyphenols per day, JUICE treatment for 17 days did not change exercise-induced alterations in inflammation and oxidative stress or immune function in trained cyclists after a 3-day period of overreaching.